Dynamic phenomena for charged clusters in cryogenic liquids - Chikina, I.; Nazin, S.; Shikin, V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
Discussed in the paper are resonance phenomena in electrolytes related to possible relative motion of the charged core and hydrate (solvate) shell of each cluster. The resonances are shown to contain important information on the internal structure of clusters. Special attention is paid to the process of formation of the cluster associated mass in the solvent.